Implementasi Undang-Undang No. 40 Tahun 1999 Tentang Pers dalam Pemenuhan Hak Asasi Manusia (Sudi Kebebasan Pers Di Propinsi Lampung) - Anggalana ANGGALANA (KEADILAN PROGRESIF, 2015)
The fact that human beings have a fundamental right,such as human rights. Of the many human rights attached to these, there is a right to obtain information, where one means to obtain the information coming from the press. The embodiment of popular sovereignty in a democratic state is the guarantee of human rights including freedom of the press, including the Indonesian nation that embraces democracy. Freedom of the press is part of the constitutional rights of citizens of Indonesia as the mandate of Article 28 of the Constitution of the Republic of Indonesia Year 1945. Of the mandate of the Constitution of the Republic  of Indonesia Year 1945, the Government of the Republic of Indonesia implements it in the form of a legislation, namely the Law of the Republic of Indonesia Number 40 of 1999 on the Press in order to provide legal guarantees for the independence and freedom of the press in Indonesia. Efforts to build a democracy with social justice and human rights guarantees necessary to have an atmosphere that is safe, orderly, peaceful, and conducted responsibly and in accordance with prevailing laws and regulations.